Long-term tillage and crop residue management in the subarctic: fluxes of methane and nitrous oxide - Cochran, Verlan L.; Sparrow, Elena B.; Schlentner, Sharon F.; Knight, Charles W. (Canadian Journal of Soil Science, 1997)
Methane and nitrous oxide are important radiatively active gases that are influenced by agricultural practices. This study assesses long-term tillage, crop residue management, and N fertilization rates on the flux of these two gases at a high latitude site representing the northern fringe of large-scale agriculture. Cumulative methane uptake for the summer was higher from no-tillage plots than tilled plots. This was associated with lower soil water contents with tillage. Thus, the reduction in CH 4 uptake was attributed to water stress on methane oxidizers. At planting, soil water contents were near field capacity, and the no-till plots had the lowest uptake which was attributed to restricted diffusion of methane to active sites. A similar pattern of methane uptake to soil water content was found with the residue management treatments. Removing the straw lowered the soil water content and for most of the season methane uptake was also lower than where the straw had been left on the plots. Nitrogen fertilizer rate had little effect on methane uptake over the summer, but high N rates lowered consumption during the time of active nitrification early in the season. This corresponded to the time of maximum efflux of nitrous oxide. Nitrous oxide efflux was greatest at the high N rate where straw was retained on the plots. Key words: Methane, nitrous oxide, nitrification, denitrification, barley